2018
DOI: 10.1177/1078155217752078
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcal infections in two patients receiving ibrutinib therapy for chronic lymphocytic leukemia

Abstract: Cryptococcal infections are responsible for significant morbidity and mortality in immunocompromised patients. Reports of these infections in patients on small molecular kinase inhibitors have not been widely reported in clinical trials. We describe one case of cryptococcal meningoencephalitis and one case of cryptococcal pneumonia in two patients who were receiving ibrutinib for chronic lymphocytic leukemia. Despite different sites of cryptococcal infection, both patients had similar presentations of acute il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Another retrospective study has shown 37.2% of patients receiving ibrutinib for lymphoid cancer developed invasive fungal infection 9. Multiple case reports also support an association of invasive aspergillosis with ibrutinib therapy,10–14 with several case reports suggesting an association with cryptococcal infection 14–20. Mucormycosis and Pneumocystis jirovecii with ibrutinib therapy have also been described 21–23…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Another retrospective study has shown 37.2% of patients receiving ibrutinib for lymphoid cancer developed invasive fungal infection 9. Multiple case reports also support an association of invasive aspergillosis with ibrutinib therapy,10–14 with several case reports suggesting an association with cryptococcal infection 14–20. Mucormycosis and Pneumocystis jirovecii with ibrutinib therapy have also been described 21–23…”
Section: Discussionmentioning
confidence: 98%
“…Recognition that TKI may predispose to invasive aspergillosis, and potentially other fungal infections, such as cryptococcosis and mucor,14–21 will allow rapid recognition of affected patients and more effective management of future cases.…”
Section: Discussionmentioning
confidence: 99%
“…31 Another study also reports tow patients with cryptococcal meningoencephalitis and cryptococcal pneumonia who were receiving ibrutinib for CLL. 219 The results of these studies suggest that a compromised innate and adaptive immunity in CLL patients and further impairments in the humoral and cellmediated immune system as a result of ibrutinib administration increase the chance of cryptococcal infection. Therefore, patients who develop acute illness and simultaneously receive ibrutinib should be examined for cryptococcal antigen.…”
Section: Cryptococcosismentioning
confidence: 99%
“…Prolongation of survival with these agents comes with the cost of increased risk of bacterial and fungal infections. Among the TKIs, ibrutinib, tofacitinib, and dasatinib carry a black box warning for opportunistic infections including pneumocystis, aspergillosis, and reactivation of tuberculosis, varicella-zoster and cytomegalovirus infections [7][8][9][10][11][12][13][14][15][16]. Sunitinib specifically targets members of the split-kinase domain family of receptor tyrosine kinases (RTKs) including the vascular endothelial growth factor receptors type1 and 2 (VEGFR 1,2), platelet-derived growth factor receptors (PDGFR α,β), fibroblast growth factor receptor (FGFR1), FMS-related tyrosine kinase (FLT3), stem cell factor receptor (c-KIT), rearranged during transfection (RET) kinase and colony-stimulating factor 1 receptor, resulting in direct and indirect B and T cell dysfunction at various levels [1,2].…”
Section: Discussionmentioning
confidence: 99%